Pseudomonas urumqiensis sp. nov., isolated from rhizosphere soil of Alhagi sparsifolia. Issue 6 (5th April 2019) - Zou, Yuanyuan; He, Shanwen; Sun, Yuping; Zhang, Xiaoxia; Liu, Yang; Cheng, Qi
Abstract : A motile, Gram-stain-negative, fusiform-shaped bacterium, designated strain T3 T, was isolated from rhizosphere soil of Alhagi sparsifolia, collected from Xinjiang, PR China. Strain T3 T grew at 15–42 °C, pH 4–9 and 1–6 % (w/v) NaCl concentrations. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain T3 T belonged to the genus Pseudomonas and showed highest similarity of 98.6 % to Pseudomonas azotifigens JCM 12708 T, followed by Pseudomonas balearica DSM 6083 T (97.8 %), Pseudomonas matsuisoli JCM 30078 T (97.7 %), Pseudomonas furukawaii KF707 T (97.7 %), Pseudomonas tarimensis CCTCC AB 2013065 T (97.3 %) and Pseudomonas indica DSM 14015 T (97.1 %). Analysis based on concatenated gene sequences of 16S rRNA, rpoB and gyrB further confirmed the phylogenetic assignment of strain T3 T . The Genome-to-Genome Distance Calculator results for P. azotifigens JCM12708 T and P. balearica DSM 6083 T were 28.7±4.4% and 24.1±2.4 %, and the average nucleotide identity scores were 81.3 and 78.1 %. The major polar lipids of strain T3 T were diphosphatidylglycerol, phosphatidylethanolamine and phosphatidylglycerol. The predominant quinone was Q-9. The major fatty acids comprised summed feature 8 (C18 : 1 ω 6 c /C18 : 1 ω 7 c ; 37.7 %), summed feature 3 (C16 : 1 ω6 c /C16 : 1 ω7 c ; 28.2 %), C16 : 0 (15.6 %), C12 : 0 (7.8 %), C10 : 0 3-OH (3.0 %) and C12 : 0 3-OH (2.6 %). The G+C content of the genomic DNA of the type strain was 65.3 mol%. It is obvious from the phylogenetic, phenotypic and chemotaxonomic data that strain T3 T represents a novel species of the genus Pseudomonas, for which the name Pseudomonas urumqiensis sp. nov., is proposed. The type strain is T3 T (=ACCC 60124 T =JCM 32830 T ).